Implementasi Sensor Ultrasonic Pada Sistem Pengontrol Volume Air dan Pembaca Debit Air Berbasis IoT - Jevan Farica; Budihardja Murtianta; Demas Sabatino (Jurnal Elektro, 2026)
This system designs a non-intrusive water flow rate reader and volume controller based on a clamp-on transit-time ultrasonic flow meter (V-mount, 4-inch pipe) using the TUF-2000M, integrated with an ESP32. The time-of-flight difference is converted into velocity, flow rate is calculated (Q = v·A), and volume is estimated through integration. The volume controller stops the flow precisely at set points of 2, 4, and 6 liters to minimize overshoot. The Blynk IoT platform provides a remote interface for set point selection and real-time monitoring (flow rate, velocity, fluid sound). Performance is evaluated based on volume error, set point achievement time, and repeatability, with quick installation and minimal pressure loss. The ESP32 microcontroller serves as the controller and data processor, supported by a relay module to control the solenoid valve's open or closed state. Testing results show a 4% error for 2 liters (within a 10% error limit), a 0.10% error for 4 liters (within a 10% error limit), and a 2.5% error for 6 liters (within a 10% error limit).